2008
DOI: 10.1175/2007jhm853.1
|View full text |Cite
|
Sign up to set email alerts
|

Rain versus Snow in the Sierra Nevada, California: Comparing Doppler Profiling Radar and Surface Observations of Melting Level

Abstract: The maritime mountain ranges of western North America span a wide range of elevations and are extremely sensitive to flooding from warm winter storms, primarily because rain falls at higher elevations and over a much greater fraction of a basin’s contributing area than during a typical storm. Accurate predictions of this rain–snow line are crucial to hydrologic forecasting. This study examines how remotely sensed atmospheric snow levels measured upstream of a mountain range (specifically, the bright band measu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
159
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 135 publications
(166 citation statements)
references
References 32 publications
7
159
0
Order By: Relevance
“…A melting-level error of 500 m can result in a 200% difference in peak flow prediction [White et al, 2002]. Previous studies interpolated ground melting elevation from atmosphere hydrometeor measurements using Doppler-profiling radar [Lundquist et al, 2008;Minder and Kingsmill, 2012]. However, the uncertainty in estimates made from these methods were at best about 300 m in the American River basin.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A melting-level error of 500 m can result in a 200% difference in peak flow prediction [White et al, 2002]. Previous studies interpolated ground melting elevation from atmosphere hydrometeor measurements using Doppler-profiling radar [Lundquist et al, 2008;Minder and Kingsmill, 2012]. However, the uncertainty in estimates made from these methods were at best about 300 m in the American River basin.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, using a dew-point temperature-based method to determine the phase of precipitation is generally less geographically dependent [Ye et al, 2013]. It has also been observed that using ground-based dew-point temperatures to determine the phase of precipitation is potentially more accurate than radar-based methods due to reduction of error associate to interpreting the radar measurement [Lundquist et al, 2008].…”
Section: Introductionmentioning
confidence: 99%
“…His equations account for: (1) Heat exchange resulting from gas, liquid, or solid phase change; (2) Change in particle mass by condensation; (3) The resulting latent heat flux from condensation; (4) Heat exchange from collision coalescence or through accretion of liquid and ice crystals; and (5) Latent heat of fusion with particles melting or freezing due to contact with each other. Detailed examples of more complicated microphysical schemes are found in e.g., Thériault and Stewart [26] or Lundquist [28].…”
Section: Hydrometeor Interactionsmentioning
confidence: 99%
“…All surface-based PPDS approaches assume a constant decrease in air temperature with height (e.g., the Climate High Resolution Model (CHRM)-7.5 °C/km) [16] and do not account for interactions either between warm and cold air masses found in the most basic mid-latitude cyclone theories, or between hydrometeors and the air as precipitation falls through the lower atmosphere [28]. Therefore, without atmospheric measurements, the most physically based surface PPDS methods can not accurately reproduce physical processes occurring between hydrometeors and the atmosphere they fall through.…”
Section: Introductionmentioning
confidence: 99%
“…However, the underlying phase prediction method and related model decisions and climate forcing data can also be important for the quality of precipitation 10 phase prediction (Harpold et al, 2017). Further complicating rain-snow transition mechanisms is storage or drainage of liquid water in the snowpacks (Lundquist et al, 2008;Marks et al, 2001). Although SNODAS assimilates MODIS imagery into the model, it does not appear to capture the finer elevation patterns we found using the MOD10A product (Fig.…”
mentioning
confidence: 99%